Preparation of mixed trialkyl alkylcarbonate derivatives of etidronic acid via an unusual route - Turhanen, Petri A.; Weisell, Janne; Vepsäläinen, Jouko J. (Beilstein Journal of Organic Chemistry, 2012)
A method to prepare four (3a–d) trialkyl alkylcarbonate esters of etidronate from P,P'-dimethyl etidronate and alkyl chloroformate was developed by utilizing unexpected demethylation and decarboxylation reactions. The reaction with the sterically more hindered isobutyl chloroformate at a lower temperature (90 °C) produced the P,P'-diester (2) as a stable intermediate product. A possible reaction mechanism is discussed to explain these methyl substitutions. These unusual reactions also clarify why it is difficult to prepare alkylcarbonate prodrugs from bisphosphonates. The compounds prepared were analysed by spectroscopic techniques.
Keywords: alkyl carbonate; bisphosphonate; etidronate; ester; synthesis